Using Assessment As Learning With Active Feedback : Effect On Student Achievement - Nurmaliati; Atika Ulya Akmali; Azmi Asra (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The use of assessment as learning is still less utilized in learning in schools, while evaluation as learning can stimulate students to reflect on their learning and take an active part in learning improvement. Assessment as Learning with active feedback, not only makes the student able to reflect on learning, but assessment as learning with this active feedback also enables the student to formulate a strategy for improving their learning with guidance, motivation, and advice from the Teacher and peers. Many studies have applied Assessment to Learning in various levels and fields of science. Therefore, this study aims to study the impact of applying assessment as learning with active feedback on high school physics material. This study is an experimental study with a Pretest-Postest Control design. Referring to the research results of the application of Assessment as Learning with Active Feed can significantly improve student performance. This study implies that the findings of this research will contribute to existing knowledge. It is important to know the impact of Assessment as Learning with active feedback on student learning performance.